Testing the Sensitivity of the Tropical Bed Bug Cimex hemipterus (Hemiptera: Cimicidae) to Deltamethrin, Phoxim and Propetamphos in Eastern Iran - Mahdi Babagolzadeh; Nadia Tayefi Nasrabadi; Elham Moghaddas; Ali Moshaverinia; Mohammad Reza Yousefi (Tehran University of Medical Sciences, 2024)
Background: Bedbugs are nocturnal ectoparasites that have made a comeback after 20 years and have become one of the main challenges for pest control methods worldwide. Monitoring chemical pesticide resistance is crucial for identifying the best bed bugs management strategies to effectively manage arthropods. This study aims to assess the susceptibility of Cimex hemipterus (Hemiptera: Cimicidae) collected from different parts of Khorasan-Razavi Province, (northeast of Iran) to deltamethrin (pyrethroid), phoxim (organothiophosphate) and propetamphos (phosphoramidate). Methods: This study was conducted from Dec 2020 to May 2021. The efficacy of three insecticides (deltamethrin, phoxim, and propetamphos) on adult C.hemipterus was assessed using a bioassay method recommended by the World Health Organization (WHO),. Concentrations of deltamethrin used were 10, 20, 40, 80, 160, 320, 640, 1280, and 2560 ppm, while concentrations of phoxim and propetamphos were 10, 40, 160, and 320 ppm. The bed bugs were continuously exposed to the insecticide for 24 hours, and mortality was assessed at regular intervals during the observation period. The concentration-response data were subjected to POLO-PC software and data were analyzed by the one-way and two-way ANOVA procedures. Results: The lethal concentration fifty values of deltamethrin, phoxim and propetamphos on the examined bed bugs were 0.551, 0.148 and 0.237 ppm, respectively. Insecticide effects of phoxim were significantly higher (P≤ 0.05) compared to each of either deltamethrin and propetamphos agents. Conclusions: The insecticide effects of phoxim against bed bugs were significantly higher compared to each of either deltamethrin or propetamphosinsecticides.